Peran Pemerintah Desa dalam Pemberdayaan Masyarakat di Desa Jlegiwinangun Kecamatan Kutowinangun Kabupaten Kebumen - Eric Farhan Thariq; Eka Rofiyanti; Dwi Agustina (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2022)
The Community Empowerment Program requires improvement and innovation to maximize community welfare and maximize social welfare in Jlegiwinangun village. Based on this background, it is necessary to examine the role of the village government in community empowerment in Jlegiwinangun village. The purpose of the study was to identify and analyze the role, obstacles, and efforts of the Jlegiwinangun Village Government in empowering the community in Jlegiwinangun Village. The theory used according to Soerjono Soekanto (2010) includes the ideal role (ideal roll), the role that should be (expected roll), the role that is actually carried out (actual roll). The study used qualitative methods with data collection techniques of observation, interviews, and documents. The results of this research are sufficient. The role of the village government is good in terms of implementing community empowerment programs. This can be seen from the program that has been running in the village of Jlegiwinangun. There are several strengths, namely that the community is less accepting of conditions and does not provide new ideas in improving human resources, and the formation of new business groups. Lack of experts in the implementation of training. Lack of education for marketing the results of the products or services produced so that they are not able to compete in the market. Lack of existing capital so that in its implementation it cannot be sustainable or stop halfway. So efforts are needed to mobilize strength in the implementation of community empowerment in Jlegiwinangun Village, namely the Government, experts from outside the village and also conducting comparative studies. The government encourages people to look for ideas for new businesses that are in accordance with local wisdom.